FORMULASI STRATEGI DESAIN DAN PERANCANGAN BRAND COMMUNICATION UNTUK STUDY CLUB AN-NAHL - az zahra, Salma; prabawa, bijaksana; yudiarti, diena (Telkom University, 2025)
Best, K. (2006). Design Management. Managing Strategy, Process and Implementation. Lausanne: Ava Academia. De Mozota, B. B. (2006). Design Management. using design to build brand value and corporate innovation Prabawa, B. &. (2015). Applying Strategic Design to Bulid Brand Value and Corporate Innovation. 178-179. Tanwar, R. (2013). Porter’s generic competive strategies. . Journal of business and management, 11-17. David, F. R. (2009). Manajemen Strategis Konsep. Jakarta: Salemba Empat. David, F. R. (2009). Manajemen Strategis Konsep. . Jakarta: Salemba Empat. Yusuf, S. (2013). Landasan Bimbingan dan Konseling. Jakarta: Remaja Rosdakarya. Basri, H. (2013). Landasan Pendidikan. Bandung: CV Pustaka Ceria. Sudijino, A. (2013). Pengantar Evaluasi Pendidikan. Jakarta: Raja Gratindo Persada